Onani-Masturbasi Perspektif Fikih dan Kesehatan: Analisis Hukum Islam Terhadap Fenomena Masturbasi Digital di Era Kontemporer - Anto Apriyanto; Febriyani (Al-Wasathiyah: Journal of Islamic Studies, 2026)
Masturbation (istimnā') has become increasingly relevant in the digital era due to the widespread availability of pornography, the emergence of Pornography, Masturbation, and Orgasm (PMO), and the use of Video Call Sex (VCS) among couples in Long Distance Marriages (LDM). This study examines the legal status of masturbation according to the four Sunni schools of Islamic jurisprudence and contemporary scholars, its medical implications, and the phenomena of PMO and VCS through the framework of maqāṣid al-sharī‘ah. This qualitative normative library research employs content analysis of the Qur'an, Hadith, classical juristic works, fatwas, and medical and psychological literature. The findings indicate that masturbation is fundamentally prohibited according to the four schools, although some scholars allow it as a legal concession to prevent adultery under exceptional circumstances. Medically, masturbation is not inherently harmful when practiced moderately, but excessive behavior associated with pornography may cause addiction and psychological disorders. Applying maqāṣid al-sharī‘ah offers a contextual Islamic legal framework for addressing contemporary sexual issues in the digital age.